Television, nation, and culture in Indonesia - Kitley, Philip, 1946- (Athens, OH : Ohio University Center for International Studies, 2000)
The culture of television in Indonesia began with its establishment in 1962 as a public broadcasting service. From that time, through the deregulation of television broadcasting in 1990 and the establishment of commercial channels, television can be understood, Philip Kitley argues, as a part of the New Order's national culture project, designed to legitimate an idealized Indonesian national cultural identity. But Professor Kitley suggests that it also has become a site for the contestation of elements of the New Order's cultural policies. Based on his studies, he further speculates on the.
Appendix I SEMINARS ON TELEVISION, 1993-1996NOTES; WORKS CITED; INDONESIAN LEGISLATION CITED; INDEX.
Includes bibliographical references (pages 385-403) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Television broadcasting -- Indonesia; Television broadcasting policy -- Indonesia; Television programs -- Indonesia; Télévision -- Indonésie.; Télévision -- Politique gouvernementale -- Indonésie.; Émissions télévisées -- Indonésie.; TECHNOLOGY & ENGINEERING -- Television & Video; PERFORMING ARTS -- Television -- History & Criticism; Television broadcasting; Television broadcasting policy; Television programs; Indonesia; Geschichte; Indonesien; Fernsehen; Televisie; Télévision -- Indonésie.; Politique de la télédiffusion -- Indonésie.; Télévision -- Émissions -- Indonésie.